A Framework for Post-Earthquake Response Planning in Emerging Seismic Regions: An Oklahoma Case Study. Issue 2 (May 2018) - Harvey, P. S.; Heinrich, S. K.; Muraleetharan, K. K.
This paper presents a framework for establishing post-earthquake response protocols in regions facing emerging seismic hazards through a case study of Oklahoma bridges. First, it establishes the need for new attenuation models for the Oklahoma area because of the poor fit of current attenuation models. Then, two methods are established to inspect bridges after an earthquake: smart inspection radii and ShakeCast. The smart radii use a modified version of theCampbell (2003) attenuation model to determine seismic demand and a trigger S 1 value to represent bridge capacity. This trigger S 1 value is validated by calculating slight HAZUS fragility curves for past earthquakes. ShakeCast is an online resource from USGS that uses real-time ground motion data (i.e., a ShakeMap) as seismic demand and modified HAZUS fragility curves to represent bridge capacity. Because of better-informed data on the ground shaking levels, ShakeCast recommends significantly fewer inspections than inspection radii, translating to cost savings for the Oklahoma Department of Transportation.